TRADISI TABOT PADA BULAN MUHARRAM DI BENGKULU: Paradigma Dekonstruksi - Endang Rochmiatun (Fakultas Adab dan Humaniora UIN Raden Fatah, 2014)
Abstract This paper will discuss the tradition of Tabot in the month of Muharram in Bengkulu. This study will use the post-structuralism approach which it is more likely as a critical attitude or approach that focuses on three aspects (abstraction, representation and interpretation). The theory will be used is Jaques Derrida's deconstruction theory. Deconstruction method is the hermeneutic method of deep suspicion, and then prove the suspicion of the existence of things that are not true, through deconstructive criticism. How to analyze the assumptions that in the text as well as the logic of thinking (logocentrism, binary opposition). Through the deconstruction of the binary opposition,it is indicated untruth thinking that the binary opposition as the concept of the real oppositional equal and mutually implicate each other. Sources written in Archiv fur Ethnographie Internationals are DDE Schmelltz, Bandle I in 1888, the Dutch colonial Orientalist imagery written about Bengkulu Society, which constructed as adherents of Shia Islam spiritualism, with analysis that ritual tradition in memory of the death of Hasan and Husain, a grandson of the Prophet Muhammad SAW, it will only be carried out by the adherents of Shia Islam. Imagery in Bengkulu public confidence issues will certainly be different if we see it by the paradigm of deconstruction. Keywords: -Tabot, -sejarah, -dekonstruksi